Analisis Kebutuhan Pembelajaran Pancasila Berbasis Case-Based Learning di Perguruan Tinggi - Hidayah, Farida Nur; Fitriani, Yustina (Cetta: Jurnal Ilmu Pendidikan, 2025)
The rapid development of the digital era demands the revitalization of Pancasila education through the development of contextual learning models that align with the characteristics of today's generation. This study aims to identify students’ needs regarding the implementation of Case-Based Learning (CBL) in the Pancasila course at the Kalimantan Institute of Technology. This research employs a descriptive quantitative approach using a survey technique involving 305 students from various study programs. Data were collected through a closed-ended questionnaire and analyzed using descriptive statistics in the form of frequency counts of student responses to illustrate the collective perceptions of the students. The results show that students prefer learning approaches that incorporate modern visual media such as videos and posters. The most preferred topics relate to current issues such as anti-corruption, gender-based violence, and radicalism, with the ideal duration for case study implementation being three to four weeks. The findings highlight the necessity of designing a CBL-based Pancasila learning model that is contextual, flexible, and interactive to enhance students’ active participation. Therefore, it is recommended that the development of the Pancasila curriculum at the Kalimantan Institute of Technology integrates digital media and contemporary issues to strengthen the effectiveness of the learning process.